2017
DOI: 10.3390/proteomes5040027
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Studies of Apolipoprotein Proteoforms and Their Role in Lipid Metabolism and Type 2 Diabetes

Abstract: Apolipoproteins function as structural components of lipoprotein particles, cofactors for enzymes, and ligands for cell-surface receptors. Most of the apoliporoteins exhibit proteoforms, arising from single nucleotide polymorphisms (SNPs) and post-translational modifications such as glycosylation, oxidation, and sequence truncations. Reviewed here are recent studies correlating apolipoproteins proteoforms with the specific clinical measures of lipid metabolism and cardiometabolic risk. Targeted mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The assay was comprised of two steps: 1) immunocapture of apoE from samples using anti-apoE antibody immobilized within a porous microcolumn inside a pipettor tip, and 2) elution and detection of the captured intact apoE with MALDI-TOF MS. This method has been utilized for the analysis of several other proteins [33,34]. The workflow for the assay is shown in Fig.…”
Section: New Assay For Simultaneous Apoe Phenotyping and Glycotypingmentioning
confidence: 99%
“…The assay was comprised of two steps: 1) immunocapture of apoE from samples using anti-apoE antibody immobilized within a porous microcolumn inside a pipettor tip, and 2) elution and detection of the captured intact apoE with MALDI-TOF MS. This method has been utilized for the analysis of several other proteins [33,34]. The workflow for the assay is shown in Fig.…”
Section: New Assay For Simultaneous Apoe Phenotyping and Glycotypingmentioning
confidence: 99%
“…The rest other three all have a core glycan chain made of an O-linked disaccharide galactose linked to N-acetylgalactosamine. ApoC3 0b is the proteoform that just contain the glycan core, while apoC3 1 and apoC3 2 contain additional one and two sialic acid residues, respectively [45]. Moreover, four major proteoforms of apoC3 differentially correlated to fasting TG levels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, four major proteoforms of apoC3 differentially correlated to fasting TG levels. It has been found that, using mass spectrometric immunoassay measurement, plasma apoC3 0a , apoC3 0b , and apoC3 1 had positive while apoC3 2 had negative relationship with fasting plasma TG [45], suggesting that analysis of individual isoforms of apoC3 could provide more comprehensive information than total plasma apoC3 concentration only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, both EVs and LPs carry glycosylated proteins with a different pattern of glycosylation. 31,32 Lectins are proteins that can reversibly and highly specifically bind glycoproteins, giving credence to use immobilized lectin, ConA, for potential EVs and LPs separation.…”
Section: Introductionmentioning
confidence: 99%